2021
DOI: 10.3389/fcvm.2020.610561
|View full text |Cite
|
Sign up to set email alerts
|

MiR-223-3p in Cardiovascular Diseases: A Biomarker and Potential Therapeutic Target

Abstract: Cardiovascular diseases, involving vasculopathy, cardiac dysfunction, or circulatory disturbance, have become the major cause of death globally and brought heavy social burdens. The complexity and diversity of the pathogenic factors add difficulties to diagnosis and treatment, as well as lead to poor prognosis of these diseases. MicroRNAs are short non-coding RNAs to modulate gene expression through directly binding to the 3′-untranslated regions of mRNAs of target genes and thereby to downregulate the protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 204 publications
0
25
0
Order By: Relevance
“…Due to the specific expression of miRNA-223-3p, it can be used as a biomarker for a variety of diseases (33,34). Studies have confirmed that miRNA-223-3p can mediate the inflammatory response of cardiovascular diseases and has potential as a biomarker for the diagnosis and treatment of cardiovascular diseases (35). Recent studies have shown that the expression level of serum miRNA-223-3p can distinguish mild cognitive impairment, AD, and Parkinson's disease, suggesting that miRNA-223-3p can be used as a non-invasive biomarker for differential diagnosis and prognosis of these neurodegenerative diseases (36).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the specific expression of miRNA-223-3p, it can be used as a biomarker for a variety of diseases (33,34). Studies have confirmed that miRNA-223-3p can mediate the inflammatory response of cardiovascular diseases and has potential as a biomarker for the diagnosis and treatment of cardiovascular diseases (35). Recent studies have shown that the expression level of serum miRNA-223-3p can distinguish mild cognitive impairment, AD, and Parkinson's disease, suggesting that miRNA-223-3p can be used as a non-invasive biomarker for differential diagnosis and prognosis of these neurodegenerative diseases (36).…”
Section: Discussionmentioning
confidence: 99%
“… 46 , 47 Additionally, recent reports recognized the detrimental role of miR-223-3p in autophagy process through suppressing NF-κB. 48 , 49 However, to the best of our knowledge, no data on miR-223-3p level in PCOS pancreas is available. Real-time PCR quantification revealed significant downregulation of miR-223-3p in the PCOS group compared with the normal control.…”
Section: Discussionmentioning
confidence: 99%
“…These miRNA were shown to contribute to an anti-inflammatory phenotype, as demonstrated by increased expression of Arg1, Il10 and Mrc1 in LPS-stimulated macrophages and reduced endothelial cell response to VEGF (69). Similarly to miR-192, studies have shown miR-21, miR-146a and miR-223 to be increased in EVs isolated from patients with COPD or other chronic diseases, such as osteoporosis, CVD and diabetes (70)(71)(72)(73)(74)(75)(76)(77). Therefore, these EV miRNA may provide a common link and potential biomarker for accelerated ageing and age-related diseases.…”
Section: Evs As Immunomodulatory Factors In Ageingmentioning
confidence: 99%